2015
DOI: 10.1039/c5cc00215j
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and characterization of molecular electrides

Abstract: Electrides are ionic compounds thus far appearing in the solid state, where the anionic part is constituted by isolated electrons. We herein provide an unambiguous computational means to distinguish electrides from similar species, proving the existence of some electrides in the gas phase. We also put forward a recipe to design new electrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(145 citation statements)
references
References 34 publications
5
136
1
3
Order By: Relevance
“…Three criteria have been proposed as necessary conditions in topological analyses of molecular electrides [61]: a nonnuclear maximum (NNM) of the electron density, a valence ELF basin, and negative values of the Laplacian of the electron density. While these criteria are fulfilled in the hP 4 and oP 8 phases of Na and K, they also fit other nonelectride metallic phases.…”
Section: A Electridesmentioning
confidence: 99%
“…Three criteria have been proposed as necessary conditions in topological analyses of molecular electrides [61]: a nonnuclear maximum (NNM) of the electron density, a valence ELF basin, and negative values of the Laplacian of the electron density. While these criteria are fulfilled in the hP 4 and oP 8 phases of Na and K, they also fit other nonelectride metallic phases.…”
Section: A Electridesmentioning
confidence: 99%
“…When Li atom is intercalated in calix[4]pyrrole (Figure ), its s ‐electron is pushed away from the alkali metal due to the action of the nitrogen‐atom lone pairs in the pyrrole rings. There is a negative value in Laplacian basin outside of the pyrrole rings and alkali atom, thus Li@calix[4]pyrrole shows an electride‐like characteristics, and this picture is corroborated by the finding of a NNA basin below the pyrrole rings …”
Section: Computational Characterizationmentioning
confidence: 76%
“…Bader's AIM topological analysis (left) and ELF = 0.75 (right) representations of Li@calix[4]pyrrole. (Reproduced with permission from Ref . Copyright 2015.…”
Section: Computational Characterizationmentioning
confidence: 99%
“…Thus modeling and synthesis of temperature and air‐stable electrides are always demanding. The characterization of electrides and to know the location of the free electrons (or a significant portion of an electron with high localization) are still very challenging for the experimental procedure , . The first principle computational studies can help a way out at this point.…”
Section: Introductionmentioning
confidence: 99%
“…The first principle computational studies can help a way out at this point. Sola and co‐workers and Dale et al have studied several molecular electrides and identified criteria to classify an electride as, (i) the existence of non‐nuclear attractors (NNA) of the electron density,, , i.e., a (3,–3) type of critical point (CP) in the molecular graph but not at the nuclear positions; (ii) presence of electron localization function (ELF) basins, , at the same region where NNAs exist; (iii) the Laplacian of the electron density [∇ 2 ρ( r )] should be negative at these NNAs; (iv) high NLO properties;, , , (v) non‐covalent interaction (NCI) index, , to identify the confined electrons. Although it is stated that the presence of NNA with negative ∇ 2 ρ( r ) is sufficient, but we will focus on all of the five properties mentioned above to characterize our system as an electride material.…”
Section: Introductionmentioning
confidence: 99%